Cytokinins in Symbiotic Nodulation: When, Where, What For?. (September 2017) - Gamas, Pascal; Brault, Mathias; Jardinaud, Marie-Françoise; Frugier, Florian
Abstract : Substantial progress has been made in the understanding of early stages of the symbiotic interaction between legume plants and rhizobium bacteria. Those include the specific recognition of symbiotic partners, the initiation of bacterial infection in root hair cells, and the inception of a specific organ in the root cortex, the nodule. Increasingly complex regulatory networks have been uncovered in which cytokinin (CK) phytohormones play essential roles in different aspects of early symbiotic stages. Intriguingly, these roles can be either positive or negative, cell autonomous or non-cell autonomous, and vary, depending on time, root tissues, and possibly legume species. Recent developments on CK symbiotic functions and interconnections with other signaling pathways during nodule initiation are the focus of this review. Trends: In addition to the well-documented positive role of CK phytohormones in nitrogen-fixing nodule inception, additional functions linked to other aspects of this symbiotic interaction have emerged. Negative CK functions in the root epidermis have been identified in relation with rhizobial infections and the NF signaling pathway mediating bacterial symbiont recognition and infection. Potential non-cell autonomous functions of CK occur at short distance between root epidermal and cortical layers and at long distance between shoots and roots in the frame of the 'autoregulation of nodulation' systemic pathway. Identifying specificities of CK pathways in the different root tissues involved in nodulation and their crosstalk with other hormonal pathways remains a challenge required for a detailed mechanistic understanding of the initial stages of symbiotic nodulation.